Dryophthorinae weevils (Coleoptera: Curculionidae) of the forest floor in Southeast Asia: illustrated overview of nominal Stromboscerini genera - Grebennikov, Vasily V. (Zootaxa, 2018)
All 13 Recent genera currently assigned to the tribe Stromboscerini are studied and illustrated based mainly on the type specimens of the type species. Nominal monotypic genus Parasynommatus Voss, 1956 from New Guinea is herein transferred to Cossoninae incertae sedis. The genus Nephius is notably dissimilar to the rest of the tribe and perhaps renders it paraphyletic. Besides the monotypic type genus endemic to Madagascar, the tribe is distributed in a triangle delimited by Japan, Sri Lanka and northern Australia; two new tribe records from continental Africa (Uganda) and the Western Hemisphere (Cuba) are reported and illustrated. Assignment of both fossil monotypic genera to the tribe was done outside of the cladistic framework and remains questionable. Judging by external similarity, the likeliest closest relative of Stromboscerini (with or without Nephius and, perhaps, Stromboscerus) is the tribe Dryophthorini with three Recent genera.